EFEKTIVITAS MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY GUNA MENINGKATKAN PEMAHAMAN KONSEP DASAR SISWA DI KELAS V (MATERI MENGENAL ORGAN PERNAPASAN MANUSIA) - Vera Hagita Sari; Regina Lichteria Panjaitan, Ali Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Problems in science learning in elementary schools often arise due to the dominance of lecture methods and the use of conventional media that make students less active and have difficulty understanding abstract concepts, such as human respiratory organs. This study aims to analyze the effectiveness of Augmented reality (AR)-based learning media in improving the understanding of basic concepts of fifth-grade students on the material. This study uses a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design involving 50 students, consisting of 30 students in the experimental class who use AR media and 20 students in the control class who study conventionally. The research instruments in the form of pretest and posttest tests, validated using Pearson correlation and Cronbach's Alpha reliability, then analyzed through Paired t-test, Independent t-test, N-Gain, and Cohen's d tests. The results showed that the use of AR media provided a significant increase in learning outcomes, with an average N-Gain of 0.6078 in the fairly effective category and an effect size of 1.92 in the large effect category, while the control class only achieved an N-Gain of 0.1625 with an effect size of 0.72. These findings confirm that AR media can provide interactive visualizations that make abstract concepts more concrete and understandable, while simultaneously increasing student engagement in learning. This research contributes to the growing body of literature on the use of immersive technology for science learning in elementary schools and supports the development of digital-based pedagogical innovations relevant to 21st-century needs.